Experience and challenges with short-term balancing in european systems with large share of wind power - Soder, Lennart (2013)
The amount of wind power in the world is quickly increasing. The background for this development is improved technology, decreased costs for the units, and increased concern regarding environmental problems of competing technologies such as fossil fuels. Some areas are starting to experience very high penetration levels of wind and there have been many instances when wind power has exceeded 50% of the electrical energy production in some balancing areas. The aims of this paper are to show the increased need for balancing, caused by wind power in the minutes to hourly time scale, and to show how this balancing has been performed in some systems when the wind share was higher than 50%. Experience has shown that this is possible, but that there are some challenges that have to be solved as the amount of wind power increases.